To Study the 99th Percentile Upper Reference Limit of High Sensitive Troponin T in adult population of Multan - Mehreen Aftab Khan, Ayesha Hafeez, Sikandar Hayat Khan, Mehmooda Altaf, Syed Twanger Hussain Hurr (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine 99th percentile upper reference limit of high sensitive Troponin T in adult population of Multan Methodology: A cross sectional study conducted in the department of chemical pathology, CMH, Multan from September 2021 to March 2022. Approval by the institutional review board was taken. Sample size was 265 cases. Results: Mean age was 46.2 + 12.7 years. 131(49.6%) were females and 134 (50%) were males. In 265 cases, there were 210 (79.24%) cases who had hs-TnT level of >2.99 ng/L and 55 (20.75%) have values of hs-TnT <3.0 ng/L. Cases having a level of <3.0 were assigned a value of 2.9 ng/L for statistical analysis. Kruskal-Wallis test was used to analyze significance in troponin level regarding age and gender. hs-cTnT values were found statistically significant between genders while non significant difference between age groups. Conclusion: hs-cTnT value was 18.20 ng/L in the study cases while these values were 30.46ng/L for males and 16.77ng/L for females. It is concluded that overall 99th percentile values of hs-cTnT are significantly higher among men as compared to women. Key words: High sensitive Troponin T, Adults, percentile